A national evaluation of the management practices of acute diverticulitis. Issue 4 (August 2017) - Khan, D.Z.; Kelly, M.E.; O'Reilly, J.; Khan, W.; Waldron, R.; Barry, K.; Khan, I.Z.
Abstract: Introduction: Diverticulitis is a common surgical admission that presents with a wide range of symptoms and severity. Overall there has been a shift to conservative management practices, including the consideration of non-antibiotic treatment approaches in select cases. Methods: A national survey of all consultant surgeons evaluating their practices was performed. Reasons for changes in management, use of radiological imaging, role of non-antibiotic treatment approaches and indications for elective surgical management were evaluated. Results: Response rate for this survey was 67.7% (n = 67/99). An overwhelming 92.5% stated that computed tomography imaging was routinely used to investigate acute presentations. Interestingly, 22.4% stated they would consider a non-antibiotic treatment approach in uncomplicated diverticulitis. Main reasons for adopting this approach was low inflammatory markers with short duration of symptoms. Co-amoxiclav was the most common antibiotic used for acute diverticulitis, with considerable variability in duration of treatment. Additionally, there was considerable heterogeneity regarding how many recurrences were necessary before surgical management was required. Conclusion: This review highlights substantial variation in the management of diverticulitis across Ireland. Shifts to non-antibiotic treatment approaches for uncomplicated cases are observed, but less so than in Northern Europe. National guidelines are required to establish uniform treatment protocols including indications for surgical resection.